Use of Mobile Applications in Developing Reading Comprehension in Second Language Acquisition-A Review Study - Blanka Klimova; Katarina Zamborova (MDPI AG, 2020)
Reading is a fundamental skill for academic success because university students need to comprehend an extensive amount of information in a short time to achieve their academic goals. However, the influx of new technologies into education has challenged the teaching of reading skills in a foreign language. The purpose of this study was to explore the effect of emerging technologies, especially mobile applications, on second language reading comprehension in the period between 1 January and 30 September 2020. Therefore, the authors of this article conducted a search of available studies on the topic, i.e., the use of mobile applications in developing reading comprehension in second language acquisition, in two databases: Web of Science and Scopus. Despite the methodological differences, the findings of all of the identified studies showed that there was an improvement in reading comprehension after the treatment with mobile applications. In addition, a positive attitude and enhanced learner motivation when using mobile apps was found in several studies. Overall, there is potential for developing research on MALL and reading comprehension for randomized control studies with larger populations and longer intervention periods.